2021
DOI: 10.3390/ijms22168393
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glycemic Variability in Cardiovascular Disorders

Abstract: Diabetes mellitus (DM) is one of the most common and costly disorders that affect humans around the world. Recently, clinicians and scientists have focused their studies on the effects of glycemic variability (GV), which is especially associated with cardiovascular diseases. In healthy subjects, glycemia is a very stable parameter, while in poorly controlled DM patients, it oscillates greatly throughout the day and between days. Clinically, GV could be measured by different parameters, but there are no guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 88 publications
0
26
0
Order By: Relevance
“…This is because there is some evidence suggesting that factors other than glucose concentration affect glycation of hemoglobin, thus questioning the validity of HbA1c as a surrogate for mean blood glucose (46). However, more research is still required to determine the ability of different glycemic parameters to predict changes in final outcomes in DM (47).…”
Section: Discussionmentioning
confidence: 99%
“…This is because there is some evidence suggesting that factors other than glucose concentration affect glycation of hemoglobin, thus questioning the validity of HbA1c as a surrogate for mean blood glucose (46). However, more research is still required to determine the ability of different glycemic parameters to predict changes in final outcomes in DM (47).…”
Section: Discussionmentioning
confidence: 99%
“…5 A and B, EF24 causes a dose-dependent increase in DCF-responsive ROS in NSCLC cells. It has been reported that ROS overproduction can activate mitochondrial morphological changes, which possesses an irreplaceable position in the regulation of cell death and apoptosis [ 23 ]. Herein, after treatment with EF24, the mitochondrial morphology in A549 cells was also determined by fluorescence immunocytochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…The possible mechanisms underlying the association between glycemic fluctuation and stroke may be multifactorial. Pathophysiologically, glucose fluctuation, particularly the short-term glycemic fluctuation has been associated with the severity of systematic atherosclerosis, possibly via the inducing oxidative stress, inflammatory cytokines, and endothelial damage [ 27 , 28 ]. Consistently, a recent cross-sectional study showed that glucose fluctuation is significantly associated with severe siphon stenosis of internal carotid artery in T2DM patients, suggesting that glucose fluctuation might be a risk factor for intracranial artery stenosis and ischemic stroke [ 29 ].…”
Section: Discussionmentioning
confidence: 99%